Consumers’ perceptions, preferences and willingness to pay for infant meat puree in China - Xiaoling Yu; Kelin Liu; Yue Cui; Changming Ma; Chaozhi Zhu; Long Xu (CyTA - Journal of Food)
This study examined factors influencing consumers’ willingness to purchase infant meat purees (IMPs) in China, based on a survey of 492 valid questionnaires. Using three machine learning algorithms, including logistic regression, we identified key predictors of purchase willingness, with logistic regression demonstrating the best performance (AUC = 0.704). Our analysis revealed that monthly income, price, and nutritional value significantly affect consumer decisions. Despite the benefits of commercial IMPs, many parents still prefer homemade options due to concerns about safety and sanitation. The findings offer valuable insights for manufacturers, helping them better meet the preferences and expectations of Chinese consumers and enhance the marketability of IMPs.